Communication Forums Christian: A Wisdom Local As Receptacle Communication Churches In Bekasi City - Suhartono Suhartono (Pusat Riset dan Inovasi Nasional, 2023)
Bekasi City Christian Communication Forum, is a forum for Christians across churches, where this forum is a forum for communication between interfaith and churches in Bekasi, such as from HKBP, GPIB, Bethel, Catholicism, this forum is a center for establishing communication between church residents who experience problems and threats related to intolerance that is rampant, especially in the Bekasi City area. The existence of a Christian education or education that breathes Christian beliefs is very beneficial. Religion began to become a part of the culture of every people. The role of the church, apart from being a message of the gospel to the unsaved, is also very important in building the spiritual life of its congregation in order to grow into a spiritually mature congregation. The objectives of this study are: 1). To find out and analyze the extent of the role of community service through the FKK Christian organization in Bekasi City. 2). To find out and analyze the problems faced, especially by the FKK Christian organization in Bekasi City. In this study, this type of research is descriptive qualitative research, that is, the data collected is in the form of words, pictures, not numbers. The purpose of descriptive research is to make a systematic, factual, and accurate description of the facts and nature of a particular population or area. The results in this study can be concluded that Religion must be a social glue, which plays a role in bridging tensions, maintaining the survival of society when faced with life challenges. In this case, religion plays a role in uniting members of society in the midst of existing plurality. Religion should promote a high sense of tolerance and love, not excessive fanaticism that thinks what we have is good and what else is bad.